2010
DOI: 10.2118/122060-pa
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality and Well Injectivity: Do Residual Oil-in-Water Emulsions Matter?

Abstract: The present work is a part of a thorough and systematic laboratory study of oil-in-water emulsion flow in porous media that we have undertaken recently to investigate the mechanisms of oil-droplet retention and its consecutive effect on permeability. One of our main objectives was to see how the in-depth propagation of producedwater (PW) residual dilute emulsion could impair the permeability during PW reinjection (PWRI). During this casework, we used granular packs of sharp-edged silicon carbide grains and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…The cores used were model granular packs composed of sharp-edged silicon carbide (SiC) grains having narrow size distribution and average size of 50 m. Before use, the SiC grains were exposed to chemical and thermal treatment to eliminate impurities such as iron particles or fi nes and to create a thin layer of silica (SiO 2 ) on their surface to make the grains hydrophilic (Buret et al 2010;Medout-Marere et al 2000). Thus, all SiC model porous media used had well-known, homogeneous, and reproducible pore structure and surface properties.…”
Section: Corefl Ood Experimentsmentioning
confidence: 99%
“…The cores used were model granular packs composed of sharp-edged silicon carbide (SiC) grains having narrow size distribution and average size of 50 m. Before use, the SiC grains were exposed to chemical and thermal treatment to eliminate impurities such as iron particles or fi nes and to create a thin layer of silica (SiO 2 ) on their surface to make the grains hydrophilic (Buret et al 2010;Medout-Marere et al 2000). Thus, all SiC model porous media used had well-known, homogeneous, and reproducible pore structure and surface properties.…”
Section: Corefl Ood Experimentsmentioning
confidence: 99%
“…According to Buret et al (2010), injectivity index ␣ can be calculated from pressure differentials. Modifying the parameters for the present CO 2 injectivity investigations leads to the following formula.…”
Section: Theoretical Aspects Of Well Injectivitymentioning
confidence: 99%
“…With large and increasing quantity of water produced in oil and gas extraction process, the environmental regulations for water discharge become more and more stringent. Produced water reinjection (PWRI) is now recognized as an important way to address this problem, as it protects environment while improving oil production (Abou-Sayed, et al, 2007;Rousseau, et al, 2008;Buret, et al, 2010). Multi-functional wells such as downhole oil water separation (DOWS) and downhole water loop (DWL) are also used or proposed to control the produced water by injecting it in-situ (Veil and Quinn, 2004;Jin and Wojtanowicz, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The oil droplets size distribution in produced water can be divided into several regions as shown in Figure 1, and the soluble oil (do<=5μm) is difficult to remove completely from the water, even treated with the advanced surface facilities (Rhee, et al, 1989;Johnson, et al, 1996). Both experimental and theoretical work has shown that even such tiny soluble oil can cause severe formation damage around injectors by oil droplet capture, especially when there is no oil saturation in the formation at the beginning of injection (McAuliffe, 1973(a); Radke, 1984a, 1986;Rege and Fogler, 1988;Zhang, et al, 1993;Ohen, et al 1996;Bennion, et al, 1998;Civan, 2007;Buret, et al, 2010). Thus it is important to understand and mathematically describe how oil capture and flow blockage develops at and away from the rock face.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation